Juventude camponesa e consumo de mídia na era digital - Pereira Filho, Marco Aurélio Marão Viana (2020)
This research addresses the consumption of media in the digital age and the centrality of communication in the contemporary social structure, marked by the capitalist production of new forms of social exclusion. The research problem seeks to understand to which extent the social structures of power in the context of late capitalism are implicated in the practices of rural youth associated with media consumption in the digital age. The aim of the research is to analyze media consumption by young peasants. For that, we first define some theoretical assumptions that contribute to the application of the adopted methodology. The theoretical postulates are: the approach of Social Uses of Media, through the mediation model of Martín-Barbero (1997), specifically the Map of Communicative Mediations of Culture; the concept of social representation (MOSCOVICI, 2003; HALL, 1997); the notion of rural as a realized social category (CARNEIRO, 2008); the conceptual definition of youth as a transition period or life cycle (WEISHEIMER, 2005). The methods adopted are the Bibliographic and Documentary Research (GIL, 2008; STUMPF, 2005); the critical Ethnography of reception, proposed by Ronsini (2003; 2011) to capture the practices of recipients in primary sources, combining the assumptions of anthropological ethnography with sociology guidelines. The empirical reality of the young people participating in this research is located in the municipality of Pedreiras / MA. As a result, we realize that the rural-urban dichotomy is really present in the informants' representations, but, although they recognize the dominance of the urban over the rural, they prefer to live in the countryside. We also find strong relationships between what the mass media represents about the urban and their perceptions about the urban, whose media representations, in their view, reinforce values associated with modernity, with which they do not identify. We also notice a lack of representations about the rural in brazilian soap operas. The few ones that represent the rural are period soap operas, which reinforces stigmas that label the rural as old or outdated.